Design and Implementation of a Candy Color Sorter Device using Microcontroller-Based Color Sensor TCS3200 - Vicananda, Ladayan Pradana; Prahasti, Saptiana Nur; Ma’ruf, Khakam; Setiawan, Rizal Justian; Darmono, Darmono (Journal of Electrical Technology UMY, 2024)
The purpose of this research is to design and implement a candy color sorter device using a microcontroller-based TCS3200 color sensor. This technology can be applied in the confectionery and fruit businesses for color-based sorting. The method used is an experimental approach that begins with a literature study, followed by hardware and software design, and device testing. The research results show that the candy sorter device was successfully designed and implemented. This device is capable of sorting candies based on red, green, and blue colors with optimal sensor detection levels. The novelty value of this research is the development of an automatic candy sorter device based on the TCS3200 color sensor, which can help reduce human workload and increase sorting process efficiency in the confectionery industry.